2020
DOI: 10.31487/j.rgm.2020.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Effect of Intraovarian Injection of Activated Autologous Platelet Rich Plasma: Serum Anti-Mullerian Hormone Levels Measured Among Poor-Prognosis In Vitro Fertilization Patients

Abstract: This registered, prospective clinical trial assessed serum anti-Mullerian hormone (AMH) patterns after treatment with activated platelet rich plasma (PRP). Patients with low ovarian reserve and/or at least 1 prior failed in vitro fertilization (IVF) cycle (n=182) received PRP injected into ovarian tissue under ultrasound guidance. Pretreatment AMH, BMI and platelet (PLT) concentration were recorded and serum AMH, follicle stimulating hormone, and estradiol were then measured at 2-week intervals for up to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…At the same time in the study by Cakiroglu et al [19] and Sills et al [22], the level of serum AMH was also found to be increased (Table 3) after intra-ovarian PRP infusion with a statistically significant difference (pvalues of <0.01 and 0.0016 for the respective studies). Sills et al [22] found platelet count as a parameter likely to predict AMH response to intra-ovarian PRP injection.…”
Section: Serum Anti-mullerian Hormone (Amh)mentioning
confidence: 64%
See 4 more Smart Citations
“…At the same time in the study by Cakiroglu et al [19] and Sills et al [22], the level of serum AMH was also found to be increased (Table 3) after intra-ovarian PRP infusion with a statistically significant difference (pvalues of <0.01 and 0.0016 for the respective studies). Sills et al [22] found platelet count as a parameter likely to predict AMH response to intra-ovarian PRP injection.…”
Section: Serum Anti-mullerian Hormone (Amh)mentioning
confidence: 64%
“…In this systematic review, we have included four studies that evaluated the effectiveness of PRP in infertile women diagnosed with decreased ovarian reserve or premature ovarian failure or menopause. Table 1 outlines the characteristics of all included studies [ 19 - 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations